2012
DOI: 10.1177/0883073812450073
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Abnormalities in Children With PHACE Syndrome

Abstract: Prior case reports have identified neurodevelopmental abnormalities in children with PHACE syndrome, a neurocutaneous disorder first characterized in 1996. In this multicenter, retrospective study of a previously identified cohort of 93 children diagnosed with PHACE syndrome from 1999 to 2010, 29 children had neurologic evaluations at ≥ 1 year of age (median age: 4 years, 2 months). In all, 44% had language delay, 36% gross motor delay, and 8% fine motor delay; 52% had an abnormal neurological exam, with speec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
2
23
2
Order By: Relevance
“…The rate of deficits reported in the current study differs from previous studies that reported neurodevelopmental abnormalities in 38% to 69% of children with PHACE syndrome . It is difficult to make comparisons across studies, because previous reports differed significantly in their methodologies and varied regarding how neurodevelopmental “abnormalities” were defined.…”
Section: Discussioncontrasting
confidence: 85%
“…The rate of deficits reported in the current study differs from previous studies that reported neurodevelopmental abnormalities in 38% to 69% of children with PHACE syndrome . It is difficult to make comparisons across studies, because previous reports differed significantly in their methodologies and varied regarding how neurodevelopmental “abnormalities” were defined.…”
Section: Discussioncontrasting
confidence: 85%
“…Although the children did not consistently score lower than the general population on most neurocognitive tests, they did score lower on language tasks . In a retrospective study of 29 children with PHACE syndrome referred for neurologic evaluations, 69% were found to have neurodevelopmental abnormalities including language delay, speech abnormalities, gross motor delay, and fine motor delay . Furthermore, over half of the children in this study with structural brain abnormalities based on magnetic resonance imaging (MRI) review had abnormal neurodevelopmental outcomes .…”
Section: Discussionmentioning
confidence: 67%
“…Management includes imaging of the cerebral vasculature to determine the risk for stroke, and propranolol may be used to treat the hemangiomas. PHACE appears to be associated with increased risk of abnormal neurodevelopmental outcome, particularly when neuroimaging abnormalities are present, though limited outcome data have been reported [53]. Nonetheless, many patients do not have severe developmental problems.…”
Section: Specific Malformations With Unknown Genetic Causementioning
confidence: 99%